Equality vs unequality of lexical cycle components (on the material of the daily cycle in the Spanish language) - Karbachova, Tatiana V. (Journal of the Belarusian State University. Philology, 2019)
Relations of between the constituents of the lexical cyclic subsystems are analyzed. It is noted that the semantics of the names of the members of the cycles, recorded in the dictionary descriptions, predetermines their interpretation as a system of equivalent elements. An analysis of the derivational and combination properties of the names of the components of the daily cycle in Spanish reveals a variety of additional semantic features in the latent area of their meanings. According to their additional semantic features, constituents of lexical cycles either appear to be opposed to each other, or unite in microgroups, or acquire a certain emphasis on the background of other elements of the cycle, to which such signs are not characteristic. This leads to the conclusion that inequality is the other side of relationships in the cyclic language subsystem.
Keywords: semantic (lexical) field; cycle; salience; equality; unequality; opposition